PENDAMPINGAN PEMBUKUAN KEUANGAN PADA UMKM DODOL NANAS ROSNAH DIDUMAI - Rispa Eliza; Yanti, Mery; Sari, Indah Maha; Septira, Ika Apia; Nasrullah, Nasrullah; Lailani Fitria (Komunitas Manajemen Kompetitif, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the local economy, yet many still face challenges in financial management, particularly in bookkeeping practices. This community engagement program aimed to enhance the financial bookkeeping capacity of Dodol Nanas Rosnah, an MSME based in Dumai, through training, the development of simplified bookkeeping formats, and hands-on implementation assistance. The methods employed included initial observation, basic accounting training, daily transaction recording support, and evaluation of bookkeeping outcomes. The results showed significant improvement in the owner's understanding and ability to record financial transactions and prepare simple financial reports. The business owner also began to recognize bookkeeping as a critical tool for decision-making and business development. Despite challenges such as limited digital literacy and time constraints, the program had a positive and sustainable impact. Similar initiatives are recommended to support other MSMEs in strengthening their financial management systems.